[18F]FDG Positron Emission Tomography for Initial Staging and Healing Assessment at the End of Therapy in Lymph Nodes and Bone Tuberculosis - Sarda-Mantel, Laure; Kaoutar, Jidar; Alfaiate, Toni; Lopes, Amanda; Paycha, Frédéric; Benali, Khadija; Mikail, Nidaa; Soussan, Michael; Lemarignier, Charles; Méchaï, Frédéric; Nagat, Sophie Le; Montravers, Françoise; et al. (Frontiers in Medicine, 2021)
Objective: In extra-pulmonary tuberculosis, therapeutic management is difficult in the absence of reliable tool to affirm healing at the end of treatment. In this prospective multicenter study we evaluated [18F]FDG-PET for this purpose. Methods: 42 patients out of 55 included patients could be analyzed. Additionally to usual biological, histological and morphological explorations, [18F]FDG-PET was performed at diagnosis (PET1), at the end of treatment (PET2), indeed 6 months later. Then patients were followed until 12 months after end of prescribed treatment. Results:PET1 was positive in 97.6% of patients and discovered unknown injured sites in 52.7% of cases. PET2 was positive in 83.3% of uncured patients, and in 82.3% of cured patients. The sum and mean value of SUVmax measured in PET/CT lesions decreased between PET1 and PET2 in all patients. Mean value of SUVmax (MSUV) and sum value of SUVmax on PET2 showed the highest AUC on ROC curves for the diagnosis of healing at the end of prescribed treatment; MSUV ˂ 3.5 on PET2 had a sensitivity of 76.5% and a specificity of 80.0% to affirm healing at the end of prescribed treatment. Conclusions: [18F]FDG-PET/CT was useful at diagnosis, discovering unknown lesions in 52.7% of cases. MSUV on PET2 was the best criteria to affirm healing at the end of prescribed treatment.